Deteksi Gen P16 pada Sampel Blok Parafin Lidah Penderita Karsinoma Sel Skuamosa Rongga Mulut di RSUD Dr. Moewardi. - Ernestine, Coraega Gena; Subiyantoro, Pradipto; Nirmala, Vita (Nexus Biomedika, 2013)
Background: Oral squamous cell carcinoma is a part of the cancer in the head and neck which ranks 10th most cancers in the world with a wide geographical distribution. It is usually found in the late stage. P16 gene (CDKN2a/INK4a) is an important tumor suppressor geneÂ  in carcinogenesis. This study aimed to detect the expression of p16 gene on paraffin block samples of the tongue of the oral squamous cell carcinoma patients in RSUD Dr. Moewardi. Methods: DNA product used in this study was isolated from 14 samples on Paraffin Blocks of the tongue of the oral squamous cell carcinoma patients in RSUD Dr. Moewardi. The DNA products, then, were used as a template for PCR amplification of the p16 gene. Primers were designed with the base sequences deposited in Gene Bank. PCR amplification products were run in agarose gel electrophoresis and visualized to detect the presence of the p16 gene. Later, the results were analyzed and presented in descriptive data. Results: Only 6 of 14 samples were diagnosed as oral squamous cell carcinoma. From 6 samples only one was detected positive expression of p16 gene. DNA bands were detected in 3% agarose gel. The intensity of DNA bands was visualized lowly and there was a smear. On the 5 other samples, DNA bands were detected under the marker, thus they showed a negative result or the expression of p16 gene was not detectable. Conclusions: Among 6 samples of the tongue of the oral squamous cell carcinoma patients, only one showed positive expression of p16 gene. Errors in the molecular and tumor differentiation level analysis was able to cause the negative results in this study. Therefore further research that detected expression of p16 gene on the tongue of the oral squamous cell carcinoma patients was needed. Keywords:P16 gene, Paraffin Block, oral squamous cell carcinoma.